PENERAPAN PEMBELAJARAN INTERAKTIF BERBASIS KEGIATAN EKSTRAKURIKULER DALAM PENGUATAN PENGUASAAN MUHADASAH DAN MUFRADĀT BAHASA ARAB SANTRI PONDOK PESANTREN AN-NAHDLOH MALAYSIA - Farhanuddin Sholeh; Erlin Indaya Ningsih; Arifatul Uyun; Muhammad Hakim Mustofa; Muhammad Husen (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
This study aims to analyze the effectiveness of implementing interactive learning based on extracurricular activities in strengthening the mastery of muhadasah (speaking ability) and mufradāt (vocabulary) of students at Pondok Pesantren An-Nahdloh, Selangor, Malaysia. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation during the International Community Service (KKN) program. The findings reveal that interactive learning integrated with extracurricular activities—such as language games, thematic conversations, and role-playing—significantly enhances students’ participation and confidence in speaking Arabic. The use of contextual learning media, such as mufradāt posters displayed around the dormitory, strengthens students’ visual memory of new vocabulary and fosters a bi’ah lughawiyyah (Arabic-speaking environment) that encourages natural language use in daily life. This study concludes that interactive, extracurricular-based learning effectively improves students’ linguistic competence while cultivating communicative, collaborative, and religious character development